2010
DOI: 10.1645/ge-2270.1
|View full text |Cite
|
Sign up to set email alerts
|

The First Report of Hepatozoon Species Infection in Leopard Cats (Prionailurus bengalensis) in Korea

Abstract: Hepatozoon species infections were detected in 4 of 5 heart samples from leopard cats (Prionailurus bengalensis) in Korea examined by light microscopy and PCR. Microscopically, the schizonts of the Hepatozoon species were observed within the parasitophorous vacuoles of unidentified host cells that were located between myocytes. The schizonts were approximately 31 +/- 4 x 19 +/- 3 microm in size; 3 mature schizonts contained approximately 24, 25, and 35 merozoites. In analyses of the partial 18S rRNA gene seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…reported from the Iriomote cat, leopard cat ( P. bengalensis ) and domestic cat which were 22·3 ± 3·1  µ m × 15·3 ± 2·2  µ m (Kubo et al 2006) and 22 ± 4·8  µ m in length (Klopfer et al 1973), respectively, and similar in size to the meronts observed in the myocardium of the leopard cat (31 ± 4  µ m × 19 ± 3  µ m, Kubo et al 2010) and lion ( Panthera leo ) (30  ×  23  µ m in length, Averbeck et al 1990). The differences in the sizes of meronts between the studies may be due to different fixation procedures used for specimens preparation, errors in measurement or even affiliation to different species or strains of Hepatozoon as already suggested (Baneth and Shkap, 2003; Kubo et al 2010). Histopathology revealed the presence of two types of developing meronts in wild cats infected with H. silvestris sp.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…reported from the Iriomote cat, leopard cat ( P. bengalensis ) and domestic cat which were 22·3 ± 3·1  µ m × 15·3 ± 2·2  µ m (Kubo et al 2006) and 22 ± 4·8  µ m in length (Klopfer et al 1973), respectively, and similar in size to the meronts observed in the myocardium of the leopard cat (31 ± 4  µ m × 19 ± 3  µ m, Kubo et al 2010) and lion ( Panthera leo ) (30  ×  23  µ m in length, Averbeck et al 1990). The differences in the sizes of meronts between the studies may be due to different fixation procedures used for specimens preparation, errors in measurement or even affiliation to different species or strains of Hepatozoon as already suggested (Baneth and Shkap, 2003; Kubo et al 2010). Histopathology revealed the presence of two types of developing meronts in wild cats infected with H. silvestris sp.…”
Section: Discussionmentioning
confidence: 87%
“…Predilection to muscle tissue has also been reported in domestic and wild cats infected with H. felis (Klopfer et al 1973; Averbeck et al 1990; Beaufils et al . 1998; Kubo et al 2006, 2010; Baneth et al 2013) and dogs and wildlife infected with Hepatozoon americanum (Vincent-Johnson et al 1997). This is substantially different from H. canis where infection is associated with the occurrence of meronts in haemolymphoid tissues (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…infection in January 2010 even though the parasitemia had not been detected in addition to the December 2010 and January 2011 captures. Furthermore, genotypic analysis of the partial 18S ribosomal RNA gene revealed 98 to 99% identity to those of H. felis isolates in leopard cats in Korea (GenBank accession numbers GQ377216-GQ377218) [15]. No information is currently available for Japanese isolates of H. felis.…”
mentioning
confidence: 99%
“…This finding suggests that the "Far East genotype" of H. felis is spreading in this area. However, Korean leopard cats already possess a non-"Far East genotype" of H. felis [15]. The Iriomote cat was estimated to have diverged from the continental leopard cat approximately 200,000 to 100,000 years ago, based on DNA analysis results [17].…”
mentioning
confidence: 99%